New Fowler Proficiency / Use of English 1 - Fowler W.S (New Editions, 2001)
The first part of a two-part course providing a graded, step-by-step approach designed to teach students how to handle each of the five types of question they will encounter in the Use of English exam. Practice Test 1, Practice Test 2, Comprehension and Summary, Appendices, Verbs Taking Prepositions, Related Words.